Shake Table Blind Prediction Tests: Contributions for Improved Fiber-based Frame Modelling. Issue 9 (1st September 2020) - Sousa, Romain; Almeida, João P.; Correia, António A.; Pinho, Rui
ABSTRACT: Distributed plasticity Euler-Bernoulli fiber beams are regularly used by researchers and practitioners to simulate the nonlinear seismic response of reinforced concrete framed structures. This study presents a sensitivity analysis, combining newly proposed and existing goodness-of-fit measures, to identify commonly used engineering modeling options that most critically influence the response accuracy. The dynamic behavior of three distinct structures tested in international blind prediction challenges is considered. Sensitivity parameters include equivalent viscous damping, element formulation, strain penetration effects, and material models. The results are critically discussed in light of theoretical shortcomings of the model assumptions.